2014
DOI: 10.2209/tdcpublication.55.95
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated Pneumonia Risk Decreased by Use of Oral Moisture Gel in Oral Health Care

Abstract: Although oral health care has a preventive effect against ventilator-associated pneumonia (VAP), the most effective method of oral health care in this respect remains to be established. The objective of this single-center, randomized, controlled trial was to investigate the relationship between VAP and various methods of oral health care. All patients included in the study (n=142) were on mechanical ventilation with oral intubation at the intensive care unit of the Tokyo Dental College Ichikawa General Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
0
11
0
4
Order By: Relevance
“…However, studies using the modified Oral Assessment Guide have shown that there are no differences in oral hygiene findings with different oral care methods [23,24,40]. In contrast, studies in which dental evaluation, such as plaque score, or objective evaluation, such as bacterial identification, were conducted have shown clear differences in results between various oral care methods, allowing for comparisons of the effects of oral care methods [41][42][43][44][45][46][47][48][49].…”
Section: Oral Hygiene Management Methods For Patients In Icusmentioning
confidence: 99%
“…However, studies using the modified Oral Assessment Guide have shown that there are no differences in oral hygiene findings with different oral care methods [23,24,40]. In contrast, studies in which dental evaluation, such as plaque score, or objective evaluation, such as bacterial identification, were conducted have shown clear differences in results between various oral care methods, allowing for comparisons of the effects of oral care methods [41][42][43][44][45][46][47][48][49].…”
Section: Oral Hygiene Management Methods For Patients In Icusmentioning
confidence: 99%
“…12 The literature recommends that oral hygiene protocols be instituted for patients with mechanical ventilation. 5,9 However, the literature is scarce regarding evaluations of the presence of biofilm in patients admitted to ICUs; this research seeks a relationship between different types of edentulous patient conditions and how these and other factors, such as gender, affect the dental element. Prior to this, it is essential to track the factors that contribute to periodontal disease.…”
Section: Original Researchmentioning
confidence: 99%
“…6 In addition, studying the systematic promotion of good oral health in patients admitted to intensive care units (ICUs) is relevant to studies on ventilator-associated pneumonia. 1,2,[6][7][8] The literature has indicated the possibility of developing ventilator-associated pneumonia 1,2,5,7,9 and that bacterial oropharyngeal colonization is an important risk factor, indicating that care in oral intervention can prevent plaque buildup, promote improvement in immunity, and reduce the possibility of developing these infections. 1,[9][10][11] Finally, it is important to evaluate the effect of research that can establish parallels between oral health factors including components of oral microbial flora immunity and dental plaque and how these variables may influence…”
Section: Introductionmentioning
confidence: 99%
“…Oral health care for older adults in long-term care facilities is important for many reasons, such as the prevention of aspiration pneumonia. 1 , 2 , 3 , 4 , 5 However, the provision of oral care in long-term care settings is often challenging, 6 , 7 , 8 with the most frequently reported problems being the refusal of care by uncooperative residents and inadequate staff knowledge or skill. 7 The refusal of care is a result of the residents' behavior, which is attributed to tactile hypersensitivity (TH).…”
Section: Introductionmentioning
confidence: 99%